Blocking 17β‐hydroxysteroid dehydrogenase type 1 in endometrial cancer: a potential novel endocrine therapeutic approach. Issue 2 (3rd January 2018) - Konings, Gonda FJ; Cornel, Karlijn MC; Xanthoulea, Sofia; Delvoux, Bert; Skowron, Margaretha A; Kooreman, Loes; Koskimies, Pasi; Krakstad, Camilla; Salvesen, Helga B; van Kuijk, Kim; Schrooders, Yannick JM; Vooijs, Marc; et al.
Abstract: The enzyme type 1 17β‐hydroxysteroid dehydrogenase (17β‐HSD‐1), responsible for generating active 17β‐estradiol (E2) from low‐active estrone (E1), is overexpressed in endometrial cancer (EC), thus implicating an increased intra‐tissue generation of E2 in this estrogen‐dependent condition. In this study, we explored the possibility of inhibiting 17β‐HSD‐1 and impairing the generation of E2 from E1 in EC using in vitro, in vivo, and ex vivo models. We generated EC cell lines derived from the well‐differentiated endometrial adenocarcinoma Ishikawa cell line and expressing levels of 17β‐HSD‐1 similar to human tissues. In these cells, HPLC analysis showed that 17β‐HSD‐1 activity could be blocked by a specific 17β‐HSD‐1 inhibitor. In vitro, E1 administration elicited colony formation similar to E2, and this was impaired by 17β‐HSD‐1 inhibition. In vivo, tumors grafted on the chicken chorioallantoic membrane (CAM) demonstrated that E1 upregulated the expression of the estrogen responsive cyclin A similar to E2, which was impaired by 17β‐HSD‐1 inhibition. Neither in vitro nor in vivo effects of E1 were observed using 17β‐HSD‐1‐negative cells (negative control). Using a patient cohort of 52 primary ECs, we demonstrated the presence of 17β‐HSD‐1 enzyme activity ( ex vivo in tumor tissues, as measured by HPLC), which was inhibited by over 90% in more than 45% of ECs using the 17β‐HSD‐1 inhibitor. Since drug treatment is generally indicated for metastatic/recurrent and not primary tumor, we next demonstrated the mRNA expression of the potential drug target, 17β‐HSD‐1, in metastatic lesions using a second cohort of 37 EC patients. In conclusion, 17β‐HSD‐1 inhibition efficiently blocks the generation of E2 from E1 using various EC models. Further preclinical investigations and 17β‐HSD‐1 inhibitor development to make candidate compounds suitable for the first human studies are awaited. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.